Pemenuhan Kebutuhan Psikologis Dasar Dalam Motivasi Jamaah Umrah Mandiri - Denianti, Laila; Muhajarah, Kurnia (Jayapangus Press, 2025)
This study aims to identify how the fulfillment of basic psychological needs, namely competence, independence, and relatedness can increase and shape pilgrims' motivation to perform Umrah independently. With the increasing public interest in performing Umrah independently, it is important to understand how these three basic psychological needs affect pilgrims' motivation. This study uses a qualitative research method with a psychological approach. Data were collected through interviews with pilgrims who have performed Umrah independently and observation. This study involved five participants who have performed Umrah independently. The results showed that pilgrims will fulfill and satisfy their three basic psychological needs such as competence, autonomy and relatedness with the help of several factors such as previous experience, technological advances, access to information, and the existence of a community. These three needs together increase and shape their motivation in performing Umrah independently so that pilgrims can undergo worship with more confidence and meaning. Motivation that increases and is formed after the fulfillment of basic psychological needs includes intrinsic motivation and extrinsic motivation. In addition, intrinsic motivation is more dominant in developing and increasing during the implementation of independent Umrah.